Dairy Products for Human Health - Savaiano, Dennis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dairy foods make up an important part of the diets of billions of people across the globe. The nutrient composition of dairy foods adds significantly to a healthy diet, as dairy foods are an excellent or very good source of calcium, high quality protein, potassium, and riboflavin. On the other hand, some research has related dairy intake to the occurrence of certain chronic diseases. The science behind the health properties of dairy foods continue to evolve. This monograph presents current research aimed and understanding the health benefits and risks from the consumption of dairy foods.